Anesthetic protocol for videolaparoscopic surgery in rabbits - Balbinotto,Rosi Pereira (2010)
PURPOSE: To describe the anesthetic protocol and the intubation technique without visualizing the trachea in rabbits, in order to enable the videolaparoscopic surgical procedure. METHODS: The experiment was performed on 33 female rabbits (Oryctolagus cuniculus), aged from 5 to 7 months. It consisted of general anesthesia and endotracheal intubation by manual palpation of the trachea of the rabbits, without using the laryngoscope, orally, for later videolaparoscopic surgical access to the abdominal cavity. RESULTS: The mean values and standard deviation of vital parameters of the animals were 223.8±15.61 beats per minute for heart rate; 35±9 movements per minute for respiratory rate; 96.94±0.99% of oxymetry and 42.82±4.02 mmHg for capnometry; 16.7±4.3 minutes for pneumoperitoneum (duration of surgery) and 1 hour and 14±8.52 minutes for time of observation (from induction to recovery from anesthesia). All animals were intubated in at most three attempts. No animals were lost after the introduction of this anesthetic technique. CONCLUSION: This protocol proved adequate, safe and easy to perform, on rabbits submitted to videolaparoscopic surgery.